UMKM in Improving The Economy of Rural Communities - Karniawati, Nia; Nurfatin, Nafisa; Cristian, Enrico; Karyana, Yayan (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2023)
The purpose of this study is to examine about the role of UMKM in the economy of rural communities. UMKM are micro, small and medium enterprises which are managed by the community on a small scale. However, it turn out that UMKM have very important role in the community’s economy. This study uses a descriptive method with a qualitative approach. The results of the study show that UMKM are the choise of rural communities in improving the family economy. This shows that UMKM are the main basis in the people’s economic sector. To increase the independence of rural communities, especially in the economic field. UMKM in Santosa Village, Bandung Regency have tried to develop into UMKM that are economically independent even though they live in a village where the average job is tea leaf picking. The motivation and enthusiasm they have as UMKM actors is very high.